Is there still yaws in Nigeria? Active case search in endemic areas of southern Nigeria. - Ngozi Ekeke; Francis S Iyama; Joseph N Chukwu; Kingsley Asiedu; Michael Marks; Babatunde Omotowo; Olanike Agwu-Umahi; Victor O Nvene; Shiloh Paul; Charles C Nwafor; Anthony O Meka; Chinwe C Eze; et al. (PLoS Neglected Tropical Diseases)
Background Yaws is a disease caused by the bacteria Treponema pallidum subspecies pertenue, which is most commonly seen among children below 15 years. In the twentieth century yaws was endemic in Nigeria but eradication strategies markedly reduced the disease burden. Currently there is minimal data on the ongoing transmission of yaws in Nigeria, despite reports of confirmed yaws cases in neighbouring West African countries. Methods We conducted both community and school-based active yaws case search among school-aged children in southeast Nigeria. Children were screened by trained community volunteers. Suspected yaws cases were clinically reviewed and tested using rapid diagnostic serological tests. Results Between February and May 2021, up to 28 trained community volunteers screened a total of 105,015 school children for yaws. Overall, 7,706 children with various skin lesions were identified. Eight (8) suspected cases of yaws were reported, reviewed and screened, but none was confirmed using rapid diagnostic tests. The four most common skin conditions identified were scabies (39%), papular urticaria (29%), tinea corporis (14%) and tinea capitis (12%). Conclusions No case of yaws was confirmed in this large population of children in south-east Nigeria. Continuous community awareness and yaws case finding activities have been recommended across Nigeria.